2006
DOI: 10.1002/eji.200526010
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic Plasmodium falciparum merozoite surface protein‐1 epitopes turn off memory T cells and interfere with T cell priming

Abstract: The leading blood-stage malaria vaccine candidate antigen, Plasmodium falciparum merozoite surface protein-1 (MSP-1) occurs in two major allelic types worldwide. The molecular basis promoting this stable dimorphism is unknown. In this study, we have shown that allelic altered peptide ligand (APL) T cell epitopes of MSP-1 mutually inhibited IFN-c secretion as well as proliferation of CD4 + T cells in 27/34 malaria exposed Gambian volunteers. Besides this inhibition of malaria-specific immunity, the same variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…24 This data clearly suggests the need for designing minimal subunit-based vaccines (preferentially synthetic ones) so as not to fall into the genetic variant-induced immunological traps described above.…”
Section: Rationale For Subunit-based Synthetic Peptide Vaccine Develomentioning
confidence: 97%
“…24 This data clearly suggests the need for designing minimal subunit-based vaccines (preferentially synthetic ones) so as not to fall into the genetic variant-induced immunological traps described above.…”
Section: Rationale For Subunit-based Synthetic Peptide Vaccine Develomentioning
confidence: 97%
“…Previous data have suggested that cohabiting P. falciparum parasites could interfere with the priming of T cell responses by the phenomenon of immune interference as well as restimulation of memory responses by immune antagonism, whereby APL epitopes present in dimorphic Ags antagonize responses to each other (38). This led to concerns about the ability to prime and boost cellular immune responses with vaccines encoding more than one allele of an Ag.…”
Section: Human Vaccination With Biallelic Ama1 and Msp1 Vaccines Indumentioning
confidence: 99%
“…4A), indicating that responses had been induced in vivo by vaccination to these epitopes and not completely prevented owing to immune interference or antagonism. In their studies, Lee et al (38) described antagonism as an arbitrary $30% reduction in the response following restimulation with both peptides. To increase stringency we increased the cut-off to a $50% reduction.…”
Section: Priming Of T Cell Responses In Unimmunized Control Volunteermentioning
confidence: 99%
See 2 more Smart Citations